Mediation: Understanding a Constructive Conflict Management Tool in the Workplace - Lourdes Munduate; Francisco J. Medina; Martin C. Euwema (Journal of Work and Organizational Psychology, 2022)

(untitled)
Mediation becomes relevant nowadays as a way to manage conflicts in the workplace in a nonjudicial way, preventing costly, extensive, and unsatisfying legal procedures. This study tries to systematize the more recent research about mediation, showing the main challenges, questions, and findings. Research suggests the importance of integrating the organizational and societal context in the study of mediation, the use of efficiency, equity, and voice objectives for evaluating mediation effectiveness, and taking into account a contingency approach in mediator strategies. There is an important gap between the large development of professional practice in mediation and the few systematic studies on this topic. This paper offers a model that considers current research and practice for mediation effectiveness. This model could be used to focus the orientation of scholars, practitioners, and governments in search of new developments in the design of mediation. Future research could explore specific combinations of these dimensions to analyze sectors, organizations, or cases of mediation.